2014
DOI: 10.2135/cropsci2013.09.0615
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Maize Kernels from a Breeding Program for Protein Quality: II. Correlatively Expressed Functional Amino Acids

Abstract: Modern maize (Zea mays L.) breeding and selection for large starchy kernels may have contributed to reduced contents of essential amino acids, including lysine, methionine, and cysteine, which represents a serious nutritional problem. We evaluated 1348 maize accessions classified into 13 populations and derived from crossing exotic, high-quality maize landraces with Corn Belt stiff-and non-stiff-stalk heterotic groups. We used multivariate statistical analyses methods and validated partial least squares regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Earlier Jaradat and Goldstein [25,26] identified sources of variation of single and multiple quality traits, determined the level of genetic diversity present in a large maize germplasm, and quantified phenotypic variation that may be useful for developing high-quality maize cultivars. Concerns are rising over the declining density of micronutrients, especially Fe and Zn, and some macronutrients (e.g., Ca and Mg) in grains of staple food and feed crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier Jaradat and Goldstein [25,26] identified sources of variation of single and multiple quality traits, determined the level of genetic diversity present in a large maize germplasm, and quantified phenotypic variation that may be useful for developing high-quality maize cultivars. Concerns are rising over the declining density of micronutrients, especially Fe and Zn, and some macronutrients (e.g., Ca and Mg) in grains of staple food and feed crops.…”
Section: Discussionmentioning
confidence: 99%
“…The R 2 values for protein, amino acids, and starch (>0.96) were logically larger than for oil (0.38), presumably due to their larger genetic components [26]. Others have found that densities of some nutrients (e.g., Mg, S, Fe and Zn) are correlated with grain protein content (GPC) [15].…”
Section: Biochemical Constituents and Nutrient Dynamicsmentioning
confidence: 97%
“…Breeders should plan their breeding strategy for developing new hybrids depending on the future demand and market requirements (Dagade et al, 2015). The nutritional quality of maize can be improved by selecting the essential amino acids through selection and breeding (Jaradat and Goldstein, 2014). Maize kernels with high methionine and lysine concentrations are important in poultry feed (Moore et al, 2008;Adeyemo, 2012).…”
Section: Introductionmentioning
confidence: 99%